Resistance of Bacillus subtilis Spores to Inactivation by Gamma Irradiation and Heating in the Presence of a Bactericide: III. Factors Affecting Rates of Inactivation by Phenylmercuric Nitrate - Deasy, P. B. (1971)
Aqueous suspensions of Bacillus subtilis NCTC 8236 spores, surviving gamma irradiation from a cesium-137 source, exhibited an enhanced rate of inactivation compared to nonirradiated spores when heated with 0.04% phenylmercuric nitrate. The enhanced rate of inactivation, observable from survival curves, was noted when spores were irradiated with 150,000 rad under air in either the presence or absence of the bactericide. The magnitude of the enhanced inactivation rate increased as the irradiation dose under air increased from 150,000 to 300,000 rad. The inactivation rates of spores surviving irradiation with 150,000 rad under either oxic or anoxic conditions did not exhibit a simple quantitative relationship. The enhancement effect was observed when the severity of the heat treatment was increased by either reducing the pH from 8 to 6 or raising the temperature from 70 to 90 C.